Penerapan Model Pembelajaran Fisika Berbasis Permainan Tic-Tac-Toe Berbantuan Media Flash Card: Application of Physics Learning Model Based on Tic-Tac-Toe Played with Flash Card Media - Nurita Sari; Effendi Effendi (Pendidikan Fisika Universitas Nurul Huda, 2026)
This study aims to find out learning outcomes through a cooperative learning model based on a tic-tac-toe game assisted by flash card media, find out the strengthening of student learning outcomes through a cooperative learning model based on the tic-tac-toe game assisted by flash card media, and find out the obstacles or difficulties of students towards the cooperative learning model based on the tic-tac-toe game assisted by flash card media. The method used in this study is Quantitative or experimental. The shape or design of this tic-tac-toe game is in the form of a board that is 3 columns and 3 rows. This research is a type of research on the application of a physics learning model based on the tic-tac-toe game assisted by flash card media in physics learning. The application was carried out by researchers and the media and was implemented to 20 students in class X of YP Yaiqli Jatimulyo II High School. The data collection techniques used are questionnaires and written tests, which are multiple choice. The data obtained were analyzed descriptively and quantitatively. The results of the study showed: 1) Based on the analysis, the media is suitable to be applied as a learning medium with the material of the principal amount, derivative quantity, units and dimensions. 2) At this stage, the researcher makes a media design (flash card), which contains material or questions.3) dissemination, at this stage the implementation is carried out in class X of YP Yaiqli Jatimulyo II High School. The results of the analysis of the application of the physics learning model based on the tic-tac-toe game assisted by flash card media in physics learning in student response by giving a questionnaire to students in grade X of YP Yaiqli Jatimulyo II High School, and have met the average score of 70% including the